Siti Manggopoh: Dalam Memori Kolektif Masyarakat Manggopoh pada Perang Brlasting 1908 - Putri Setiani, Natasya; Fatimah, Siti (YASIN, 2025)
This study examines the collective memory of the Manggopoh community regarding the 1908 Manggopoh War in Agam Regency, West Sumatra, with a focus on the local heroine Siti Manggopoh. The background of this research lies in the declining awareness among younger generations about local history and the figure of Mandeh Siti as a key leader in the resistance against Dutch colonialism. The aim of this study is to explore how the Manggopoh community constructs and maintains collective memory of Siti Manggopoh across generations. A historical approach was employed, involving four main stages: data collection, source criticism, interpretation, and historical writing. The findings reveal a generational difference in how Mandeh Siti is remembered. Older generations hold a strong and emotional memory rooted in oral traditions passed down within families and communities. In contrast, younger generations primarily learn about Mandeh Siti through school lessons and ceremonial activities, with less emotional attachment. These findings suggest that collective memory of local historical figures tends to shift over time and is influenced by the mediums through which information is conveyed. The conclusion of this study is that preserving collective memory requires intergenerational and contextual approaches, including the revitalization of oral traditions and the meaningful integration of local history into educational curricula.